Risk Factors for Dehiscence of Stapled Functional End‐to‐End Intestinal Anastomoses in Dogs: 53 Cases (2001–2012). Issue 1 (13th November 2015) - Snowdon, Kyle A.; Smeak, Daniel D.; Chiang, Sharon
Abstract : Objective: To identify risk factors for dehiscence in stapled functional end‐to‐end anastomoses (SFEEA) in dogs. Study Design: Retrospective case series. Animals: Dogs (n = 53) requiring an enterectomy. Methods: Medical records from a single institution for all dogs undergoing an enterectomy (2001–2012) were reviewed. Surgeries were included when gastrointestinal (GIA) and thoracoabdominal (TA) stapling equipment was used to create a functional end‐to‐end anastomosis between segments of small intestine or small and large intestine in dogs. Information regarding preoperative, surgical, and postoperative factors was recorded. Results: Anastomotic dehiscence was noted in 6 of 53 cases (11%), with a mortality rate of 83%. The only preoperative factor significantly associated with dehiscence was the presence of inflammatory bowel disease (IBD). Surgical factors significantly associated with dehiscence included the presence, duration, and number of intraoperative hypotensive periods, and location of anastomosis, with greater odds of dehiscence in anastomoses involving the large intestine. Conclusion: IBD, location of anastomosis, and intraoperative hypotension are risk factors for intestinal anastomotic dehiscence after SFEEA in dogs. Previously suggested risk factors (low serum albumin concentration, preoperative septic peritonitis, and intestinal foreign body) were not confirmed in this study.